Concept and Methodological Aspects of Providing Balanced Innovative Development of Transportation System of the Russian Federation - I. N. Geraskina; L. P. Goncharenko (Наука и техника)
The growth of significance for innovative economic development of the Russian Federation determines necessity of deeper investigation of properties and specific features of its subsystems functioning, content and forms of their inter-action, search for increasing efficiency of control systems. The transportation system is the most important strategic link of social and economic development of the country, one of the most dynamic, multiplicative and promising segments of the market, which makes 12.5 % of the gross domestic product (GDP) of the Russian Federation. An analysis of transport activity has demonstrated a smoldering recession over the last years which is accompanied by reduction of values for the most important resulting indicators. Strategic benchmarks of developing transportation activity are objectified by the consumers’ demands not only in safe, but in comfortable life medium with high environmental characteristics and aesthetic requirements. The satisfaction of such requirements is possible under condition of large-scale modernization of transportation sphere with the use of breakthrough scientific and technical solutions in all segments of human activity. All this can afford ground that it is necessary to change fundamentally an approach to investigating properties, peculiarities and factors of the transportation system development that provokes modernization of the control system for providing a balanced innovative trend and high standards of population life quality. The results of the investigations have shown that important factors of transportation system development are the following: fair competition, freedom of economic activity, development of market mechanisms, corporate culture and moral values. Study of functioning and scientific approaches to balancing innovative development of the transportation system of the Russian Federation has made it possible to create a conceptual vision and methodological basis with due account of main principles of systems theory, self-organization and synergetics and present it in brief in the given paper.